Ideological intractability in international politics of climate change (Andamios, Revista de Investigación Social, 2015)
In this article, the ideological disputes and conflicts taking place around the issue of climate change in international negotiations and politics in general are analyzed. The aim of this article is to frame the ideological clashes in climate change negotiations within the theoretical framework of Intractability. Based on this framework, those points vulnerable of intractable conflict are identified in order to avoid falling into them or to reframe the issue at stake to solve protraction in climate negotiations.
Keywords: Climate change; climate change international negotiations; ideology; intractability; risk perception